2001
DOI: 10.1002/bate.200102600
|View full text |Cite
|
Sign up to set email alerts
|

Das Belastungsfahrzeug BELFA für die experimentelle Tragsicherheitsbewertung von Massivbrücken und Abwasserkanälen

Abstract: Mit dem Ziel, Belastungsversuche unter Anwendung der Methode der experimentellen Tragsicherheitsbewertung (EXTRA) an Massivbrücken und Abwasserkanälen rationell durchführen zu können, entwickelte eine Forschergruppe der Hochschulen Bremen (federführend), TU Dresden, HTWK Leipzig und Bauhaus‐Universität Weimar in Zusammenarbeit mit der Firmengruppe Eggers und weiteren Firmen ein spezielles, flexibles einsetzbares Belastungsfahrzeug BELFA, Gegenstand des vorliegenden Beitrags sind die Vorstellung wesentlicher As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Using such vehicles, it was possible to apply loading representative for the special permit vehicles driving on Danish roads and, thus, accurately reflect the ax configurations of the Danish classification system [21]. The loading setup was quit lar to that of the BelFa loading vehicle [63,64], but BelFa usually operates at lowe Using such vehicles, it was possible to apply loading representative for the heavy special permit vehicles driving on Danish roads and, thus, accurately reflect the axle load configurations of the Danish classification system [21]. The loading setup was quite similar to that of the BelFa loading vehicle [63,64], but BelFa usually operates at lower load levels, and the increased availability of the standard transport vehicles must be considered a significant benefit.…”
Section: Loading With Special Transport Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using such vehicles, it was possible to apply loading representative for the special permit vehicles driving on Danish roads and, thus, accurately reflect the ax configurations of the Danish classification system [21]. The loading setup was quit lar to that of the BelFa loading vehicle [63,64], but BelFa usually operates at lowe Using such vehicles, it was possible to apply loading representative for the heavy special permit vehicles driving on Danish roads and, thus, accurately reflect the axle load configurations of the Danish classification system [21]. The loading setup was quite similar to that of the BelFa loading vehicle [63,64], but BelFa usually operates at lower load levels, and the increased availability of the standard transport vehicles must be considered a significant benefit.…”
Section: Loading With Special Transport Vehiclesmentioning
confidence: 99%
“…The loading setup was quit lar to that of the BelFa loading vehicle [63,64], but BelFa usually operates at lowe Using such vehicles, it was possible to apply loading representative for the heavy special permit vehicles driving on Danish roads and, thus, accurately reflect the axle load configurations of the Danish classification system [21]. The loading setup was quite similar to that of the BelFa loading vehicle [63,64], but BelFa usually operates at lower load levels, and the increased availability of the standard transport vehicles must be considered a significant benefit. The Danish classification system specifies that two adjacent vehicles should be applied [21], a standard vehicle A and a standard vehicle B.…”
Section: Loading With Special Transport Vehiclesmentioning
confidence: 99%
“…In Denmark, a method to apply loading in two lanes is used, to represent the vehicles from national codes . In Germany, a special vehicle (BELFA -Belastungsfahrzeug) was developed, which can be used to apply large loads necessary for proof load testing (Hochschule Bremen -City University of Applied Sciences, 2018, Bretschneider et al, 2012, Steffens et al, 2001. In terms of instrumentation, the recent developments are also applicable to diagnostic load testing.…”
Section: Recent Developments In Proof Load Testingmentioning
confidence: 99%
“…Vlijmen Oost carries three lanes, De Beek originally carried two lanes but is restricted to one lane, and the Halvemaans Bridge and Zijlweg carry a single lane. Vlijmen Oost was tested with a loading truck (Steffens et al, 2001) whereas the other bridges were loaded with a system of a steel spreader beam, counterweights, and hydraulic jacks. The proof load tests on the Halvemaans Bridge and viaduct Zijlweg directly showed that these structures fulfill the code requirements.…”
Section: Field Testsmentioning
confidence: 99%